Underivative duty British moral philosophers from Sidgwick to Ewing - Hurka, Thomas, 1952- (Oxford : Oxford University Press, 2011)
A team of eminent contemporary philosophers present the first collective study of seminal British moral thinkers of the late 19th and early 20th centuries. Some, like Henry Sidgwick and G.E. Moore, are already recognised as leading philosophers of their day. Others, like Hastings Rashdall and A.C. Ewing, are unjustly neglected.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Ethicists -- Great Britain; Ethics -- Great Britain -- History -- 19th century; Ethics -- Great Britain -- History -- 20th century